2021
DOI: 10.3390/buildings11100493
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Socio-Demographic and Urban Form Indices in Demand Forecasting Models to Reflect Spatial Variations: Case Study of Childcare Centres in Hobart, Australia

Abstract: This study investigated whether indices for socioeconomic, demographic and urban form characteristics can reflect the overall effect of each category in a demand forecasting model. Regression equations were developed for trip generation of the land use of long day care centres (LDCC) in the metropolitan region of Hobart, Australia, to estimate the morning peak hourly private car trip generation of the centres. The independent variables for the model were functions of socioeconomic, demographic and urban form r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Similarly, the spatial characteristics of the internal environment of blocks include factors such as form, facilities, and boundaries [56]. In recent literature, Mousavi et al found using a crowd prediction model that the density and compactness of blocks can affect population distribution [57]. Ratti et al found using location-based services data that the quality of a landscape can affect the activity and behaviour of crowds [58].…”
Section: Composition and Indicators Of Spatial Characteristicsmentioning
confidence: 99%
“…Similarly, the spatial characteristics of the internal environment of blocks include factors such as form, facilities, and boundaries [56]. In recent literature, Mousavi et al found using a crowd prediction model that the density and compactness of blocks can affect population distribution [57]. Ratti et al found using location-based services data that the quality of a landscape can affect the activity and behaviour of crowds [58].…”
Section: Composition and Indicators Of Spatial Characteristicsmentioning
confidence: 99%